Luther and Gender: Shifts in Paradigms and Orientations. Issue 2 (June 2017) - Stjerna, Kirsi I.
Abstract: Considering the tenderness and detail with which Luther attends to matters "all about Eve" in his Genesis lectures—and how he treats the matriarchs in the Genesis narrative—we can say that gender and women constitute a central interest for the reformer. He developed, in his context, a new theological anthropology that valued women's biological distinction, difference within sameness in creation, and absolute equality in redemption and callings. While his gender ideology is a work in progress, Luther's instincts are modern, if not even feminist, when placing the uterus at the central place of the delivery of the saving incarnate Word.